ANALISIS HUBUNGAN FAKTOR USIA, AKTIVITAS FISIK DAN ASUPAN MAKAN DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS WILAYAH KERJA TANGERANG SELATAN - Thresya Febrianti; Mustakim Mustakim (Collaborative Medical Journal, 2019)
Poor diet, namely sodium intake, fat intake, and lack of fruit and vegetable intake can increase the risk of hypertension. In Indonesia hypertension is still a public health problem and is experiencing an increase in new cases every year. The purpose of this study was to look at the relationship between physical activity and eating habits with the incidence of hypertension in the South Tangerang Working Area Health Center. This study was an observational analytic study using case control design. This study uses secondary data of Surkesdas FKM UMJ in 2018. Case samples in the study were respondents who had been diagnosed with hypertension by as many as 125 health care workers and controls who were not experiencing hypertension as much as 125. The sampling technique using total sampling. The results showed that there was a significant relationship between age and the incidence of hypertension (p value = 0.01 and OR = 2.76 (95% CI = 1.57-4.86)) and there was a significant correlation between physical activity and the incidence of hypertension. (p value = 0.00 and OR = 4.46 (95% CI = 2.29-67.67)). There was no significant relationship between eating salty, eating fatty foods, eating food, eating vegetables and eating fruit with the incidence of hypertension (p value> 0.05). The community is expected to carry out physical activities at least 3 times a week on a regular basis, especially in the age group â‰¥ 40 years.